Age and pre quit-day attrition during smoking cessation treatment. Issue 5 (2nd September 2020) - Conroy, Haley E.; Jacquart, Jolene; Baird, Scarlett O.; Rosenfield, David; Davis, Michelle L.; Powers, Mark B.; Frierson, Georita M.; Marcus, Bess H.; Otto, Michael W.; Zvolensky, Michael J.; Smits, Jasper A. J.
ABSTRACT: The present study aimed to replicate the finding that younger age predicts higher pre quit-day attrition. Our second aim was to explain this relation by examining empirically and theoretically informed age-related risk factors for low smoking cessation treatment engagement. 136 participants ( M age = 44.2 years, SD = 11.3 years; age = 22–64 years) were randomized to 15-weeks of either 1) an exercise intervention ( n = 72) or 2) a wellness education control condition ( n = 64). First, a logistic regression analysis was employed to test whether younger adults were more likely than older adults to drop prior to quit date. Next, we assessed whether smoking related health concerns, social expectancies, and/or perceived severity of craving affected the strength of the relation between age and attrition, by adding these three variables to the logistic regression along with age. The logistic regression model indicated that younger age and treatment condition were significantly related to the odds of dropping from treatment prior to the scheduled quit date. Further, health concerns, social expectancies, and/or perceived severity of cravings did not account for the effect of age on pre quit-day attrition. These findings highlight the importance of identifying empirically and theoretically informed variables associated with the pre quit-day attrition problem of young smokers.